2022
DOI: 10.1002/admt.202200429
|View full text |Cite
|
Sign up to set email alerts
|

4D Biofabrication of T‐Shaped Vascular Bifurcation

Abstract: Abstract4D Biofabrication – a pioneering biofabrication technique – involves the automated fabrication of 3D constructs that are dynamic and show shape‐transformation capability. Although current 4D biofabrication methods are highly promising for the fabrication of vascular elements such as tubes, the fabrication of tubular junctions is still highly challenging. Here, for the first time, a 4D biofabrication‐based concept for the fabrication of a T‐shaped vascular bifurcation using 3D printed shape‐changing lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…They found that UV exposure strengthened the construct, but longer exposure decreased the tube diameter; besides, increasing gelatin concentration increased the thickness of the films. [166] Tiny tubular structures used to treat constricted vessels, for example, BVs are called stents. [167] Nearly half of the stents used are shape-memory alloys, nitinol being an example.…”
Section: D Bioprintingmentioning
confidence: 99%
“…They found that UV exposure strengthened the construct, but longer exposure decreased the tube diameter; besides, increasing gelatin concentration increased the thickness of the films. [166] Tiny tubular structures used to treat constricted vessels, for example, BVs are called stents. [167] Nearly half of the stents used are shape-memory alloys, nitinol being an example.…”
Section: D Bioprintingmentioning
confidence: 99%
“…Recently, an exciting and intensively explored area of research in advanced biomaterials is prototyping/fabrication systems [ 43 ]. The advantages of biofabrication are complete control of the geometry and porosity of materials and no need to use additional porogen to obtain a scaffold.…”
Section: Selected Biomaterials Based On Cage-like Silsesquioxanesmentioning
confidence: 99%
“…B‐I) Adapted under the terms of the CC‐BY Creative Commons Attribution 4.0 International license ( https://creativecommons.org/licenses/by/4.0). [ 118 ] Copyright 2022, The Authors, published by Wiley‐VCH. B‐II) Adapted with permission.…”
Section: Self‐assembly and Interconnection Of (Folded) Microelectroni...mentioning
confidence: 99%
“…Secondly, SMARTLETs can also roll or fold up to contain chemical fluids without leakage as demonstrated already. [118,145] Thus, they can contain chemical resources and prevent access to external chemicals to their interior. It remains to be demonstrated that self-assembled SMARTLETs can make tight seals to retain fluids in folded sheets.…”
Section: How This Technology Addresses the Core Functions Of Cells An...mentioning
confidence: 99%